Adaptive Droop Control of the VSC-MTDC Distribution Network Considering Power–Voltage Deviation - Li, Yang; Zhao, Jianjun; Liu, Huan; Kong, Qiankun; Zhao, Yanhui; Cheng, Long; Wang, Zhenhao (Frontiers in Energy Research, 2022)
In order to realize the unbalanced power optimally allocated and the DC voltage stably controlled after disturbance, an adaptive droop control method considering power and voltage deviation is proposed based on the traditional voltage–power droop control of a voltage source converter-based multi-terminal direct current (VSC-MTDC) distribution network. The inherent constraint that the unbalanced power is proportionally distributed according to its capacity under the traditional droop control is broken in the proposed method to realize the reasonable transfer of unbalanced power and to reduce the overload risk of smaller capacity VSCs; the “dead zone” is appropriately set to relax the operating range of the VSC to a certain extent by a power deviation factor being introduced in the droop characteristic curve. The corresponding MATLAB/Simulink simulation model of the five-terminal DC power distribution network is established and compared with the electromagnetic transient model under the traditional droop control. Finally, the simulation results verify the effectiveness and control effects of the proposed control method.